2011
DOI: 10.1161/atvbaha.111.232827
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-2 Modulates Stress Response of Endothelial Cells to Oxidized Phospholipids and a Bacterial Quorum–Sensing Molecule

Abstract: Objective Chronic infection has long been postulated as a stimulus for atherogenesis. Pseudomonas aeruginosa infection has been associated with increased atherosclerosis in rats, and the bacteria produce a quorum-sensing molecule 3-oxo-dodecynoyl-homoserine lactone (3OC12-HSL) that is critical for colonization and virulence. Paraoxonase 2 (PON2) hydrolyzes 3OC12-HSL and also protects against the effects of oxidized phospholipids thought to contribute to atherosclerosis. We now report the response of human aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
2
29
0
1
Order By: Relevance
“…PON2 is expressed intracellularly, is widely found in mammalian tissues and cell types, and efficiently hydrolyzes 3OC12 to 3OC12 acid (20)(21)(22)(23)(24)(25). Independent of its hydrolytic activity, PON2 also has antioxidant activity and can protect cells from endoplasmic reticulum (ER) stress, including ER stress induced by 3OC12 (22,23,26).…”
mentioning
confidence: 99%
“…PON2 is expressed intracellularly, is widely found in mammalian tissues and cell types, and efficiently hydrolyzes 3OC12 to 3OC12 acid (20)(21)(22)(23)(24)(25). Independent of its hydrolytic activity, PON2 also has antioxidant activity and can protect cells from endoplasmic reticulum (ER) stress, including ER stress induced by 3OC12 (22,23,26).…”
mentioning
confidence: 99%
“…Kim et al (20) confirmed that 50 µM 3-oxo-C12-HSL effectively induces UPR and activates UPR target genes, such as C/EBP β and CHOP in HAECs. Therefore, the mRNA expression of representative target genes of UPR activation, such as C/EBP β and CHOP, was analyzed using qRT-PCR to determine whether 6.25 µM 3-oxo-C12-HSL was able to efficiently activate these genes ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies demonstrated that UPR-mediated induction of CHOP reduces inflammatory cytokine secretion and NF-κB activation (18,19). A recent study also demonstrated that 3-oxo-C12-HSL may induce the expression of UPR genes, such as C/EBP β and CHOP, in human aortic endothelial cells (HAECs) (20). These data strongly indicate that 3-oxo-C12-HSL may inhibit NF-κB activity through the induction of UPR.…”
Section: Introductionmentioning
confidence: 87%
“…Contrary to the literature, the paroxinase PON2 was not expressed in lower levels in the airways of non-CF bronchiectasis subjects in this study. PON2 degrades 3-oxo-C12-HSL via lactonlysis [112].…”
Section: Discussionmentioning
confidence: 99%
“…3-oxo-C12-HSL [108] and PQS [109] act on the NFκB pathway in a number of postulated ways, dependent upon the cell type and type of cellular stimulation. Interference with IκB, inhibition of peroxisome proliferator-activated receptor gamma (PPARγ) [111] and interference with host protein translation via induction of the unfolded protein response [112] are all mechanisms by which 3-oxo-C12-HSL may modulate responses in mammalian cells.…”
Section: Cell Culturementioning
confidence: 99%